Pemanfaatan Tren Tagar Welcome to Indonesia Pada TikTok Sebagai Sarana Kritik Sosial Generasi Y dan Z - Ariestuti, Ni Kadek Mawar; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium; Vol 3 No 2 (2022): Jurnal Ilmu Komunikasi Vol 3 No 2 Tahun 2022, 2023)
The use of hashtags on social media was initially used to classify content or conversation topics to make them easier to find. But now, hashtags functioned as a sign-system to respond to a phenomenon or social issue that is currently happening. Tiktok is exploring its popularity as the most popular social media platform for generation Y and Z today. Hashtags on TikTok can be used to voice the latest hot issues and trends. One of them is #welcometoindonesia, which experienced a trend from late June to early July 2021. This study uses the new media theory of Pierre Levy and the critical discourse analysis method of Teun A. Van Dijk. Through the #welcometoindonesia trend, generations Y and Z try to criticize the attitudes and habits of the majority people who dominate in social life. The dynamic conditions of social, cultural and political life can be displayed through a simple lyrics and content packaging.   Keywords : #welcometoindonesia, critical discourse analysis, social criticism, TikTok